Sejarah dan Perkembangan Metodologi Al-Nahw Al-'Arabi: Analisis Historis dari Mazhab Basrah hingga Mesir - Adilah, Aisyah; Khikmah, Eka Nur; Khalilullah, M. Zain (Kalimatuna: Journal of Arabic Research, 2024)
This research explores the historical development of the methodology (manhaj) in Arabic grammatical studies (Al-Nahw Al-'Arabi). The study highlights how interactions between Arabic and foreign languages, the emergence of the lahn phenomenon, and the evolution of grammatical schools shaped the discipline. Starting from Basrah, the study traces the spread of nahwu scholarship to Kufa, Baghdad, Andalusia, and Egypt, analyzing shifts in methodological approaches—from descriptive to normative frameworks. Using a descriptive qualitative approach, this research synthesizes data from literature, including books, journals, and articles. The findings reveal that methodological transitions reflect both intellectual debates among classical scholars and the socio-cultural contexts of their time. This study underscores the importance of understanding historical methodologies to enrich contemporary Arabic linguistics and pedagogy.